Impact of chemotherapy on expiratory muscle strength in stage 1 head and neck cancer patients - Shindikar, Yashshree J.; Diwate, Abhijit D.; Das, Arijit K. (International Journal Of Community Medicine And Public Health, 2024)
Head and neck cancer (HNC), in current days, is one of the fatal diseases. Chemotherapy is one of the main treatments for cancer. Chemotherapy has an adverse impact on the respiratory parameters of patients. In these patients, expiratory force-generating capacity is impaired, which usually helps the patients cough effectively for airway clearance. Thus, as an impact of chemotherapy, airway clearance is affected in HNC patients. This study aimed to evaluate the impact of chemotherapy expiratory muscle strength in stage 1 head and neck cancer patients. We conducted an observational study including 15 patients with stage 1 HNC in the department of oncology in a tertiary care teaching hospital. The outcome measure included assessment of the expiratory muscle strength by measuring maximum expiratory pressure. In our study, we found a result showing a significant decline of 53.43% in maximum expiratory pressure values after 3-6 months of required chemotherapy sessions. The results of the current study suggest that chemotherapy has a deleterious impact on the expiratory muscle strength in stage 1 HNC patients after long-term exposure.